Mitigation of Murabahah Financing Risks in the Nusa Bangsa Sejahtera Gresik Savings and Loans and Financing Cooperative (KSPPS) - Isnaini Maulidatu Nisa; Mustofa (al-Afkar, Journal For Islamic Studies, 2024)
Economic growth in Indonesia is now more advanced, various bank and non-bank financial institutions are competing in their operations. Risk is something that cannot be avoided by financial institutions, especially Islamic financial institutions. It is important to know that Islamic financing, which refers to the provision of funding to the public in accordance with sharia principles, has the potential to contribute to the progress and prosperity of the business world, both in terms of material and non-material success. Cooperatives are one of the destinations for MSMEs in meeting their business capital needs. In this case, of course, the Cooperative has risks related to the distribution of financing funds to MSMEs. This study aims to determine the implementation of risk management in non-bank financial institutions. This research uses a qualitative method, the data obtained is through interviews, as well as observation. Koperasi (KSPPS) Nusa Bangsa Sejahtera (Nusantara) Gresik provides murabahah financing for MSMEs that require additional business capital, the amount issued by the Cooperative is not more than 10 million rupiah. Related to murabahah financing, Nusantara Cooperative conducts risk identification management and several obstacles arise, limited amount of capital, members receive money directly, bad credit, mudharib lacks understanding of muamalah, and marketing constraints. As a mitigation that has been carried out by the Cooperative is the application of the 5C principle, conducting socialization related to Cooperative financing products, diverting bad installment payments to savings funds, helping the promotion of MSME businesses through social media, and evaluating Cooperative staff on the terms of financing application requirements. In the future, it is expected to be more thorough in the process of applying for financing, and comply with all regulations set by the cooperative.